2012
DOI: 10.1159/000332013
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance of Conventional HIV-1 Phenotyping (Antivirogram®) and Genotype-Based Calculated Phenotyping Assay (virco®TYPE HIV-1) on Protease and Reverse Transcriptase Genes to Evaluate Drug Resistance

Abstract: Objectives: A wide array of monitoring tests is commercially available to gauge HIV-1 disease progression and the overall health status of an HIV-1-infected patient. Viral load tests provide a picture of viral activity, while CD4 cell counts shed light on the immune status and can help physicians to prevent the development of opportunistic infections in patients. On the other hand, genotypic and phenotypic resistance testing and therapeutic drug monitoring help to optimize HIV-1 antiretroviral therapy. Resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Each experiment used the NL4.3 HIV-1 strain as control. For comparison, an in vitro phenotypic resistance assay that measures the level of resistance of recombinant HIV-1 from plasma samples was performed using Antivirogram assay [11]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each experiment used the NL4.3 HIV-1 strain as control. For comparison, an in vitro phenotypic resistance assay that measures the level of resistance of recombinant HIV-1 from plasma samples was performed using Antivirogram assay [11]. …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, phenotypic assays measure HIV-1 viral replication in cells cultured in different drug concentrations. There are two types of phenotypic assays: commercially available phenotypic assays generate chimeric viruses by homologous recombination of PCR-derived sequences and then culture with cells in different drug concentrations [10, 11] and in-house phenotypic assay use peripheral blood mononuclear cells (PBMCs) to isolate HIV-1 and then incubate them in target cells (MAGIC-5 cells) with different drug concentrations [12, 13]. It has been reported that phenotypic drug resistance using recombinant virus assay was limited to detect low-frequency viral quasispecies below than 50% [14].…”
Section: Introductionmentioning
confidence: 99%
“…No molecular cloning step is involved in this phenotyping assay, and a panel of recombinant strains is created to reflect the diversified viral population circulating in the patients. The assay compares the replicative capacity between the wild-type virus and the constructed virus to determine the IC 50 of the antiretroviral drugs [59]. Both assays can readily assess the drug susceptibility of a patient with viral load over 500 copies/ml.…”
Section: Cd4 + T-lymphocyte Enumerationmentioning
confidence: 99%
“…In combining the advantages of both genotyping and phenotyping, a third hybrid approach, the VircoTYPE™ HIV-1 test (Virco BVBA, Beerse, Belgium), comprises not only genotyping technique but also phenotypic ana lysis. It is a modified version of VirtualPhenotype-LM and uses linear regression modeling with over 80,000 pairs of correlated genotypic and phenotypic samples for accurate drug susceptibility prediction [59]. This approach provides a third option for drug resistance monitoring by obtaining phenotypic information from genotyping only.…”
Section: Cd4 + T-lymphocyte Enumerationmentioning
confidence: 99%
“…org), see also Thielen and Lengauer [5] and Lengauer [6] , Virco (http://vircolab.com/) in Pattery et al [7] and HIV-GRADE (http://www.hiv-grade.de/cms/grade/) in Obermeier et al [8] .…”
Section: Introductionmentioning
confidence: 99%